DESAIN DAN ANALISIS SISTEM PEMBUANGAN PANAS RESIDU PASIF PADA MOLTEN SALT REACTOR EXPERIMENT (MSRE) 10 MW - Siti Nurhasanah (UIN Sunan Gunung Djati Bandung, 2021)
As one of the Generation IV reactors, the Molten Salt Reactor (MSR) has the advantage of meeting safety requirements. To enhance the inherent safety, it is necessary to develop a conceptual design of a passive residual heat removal system for the 10 MW Molten Salt Reactor Experiment (MSRE) designed by Oak Ridge National Laboratory (ORNL). The principle, main components and design parameters of the system were discussed, and the thermalhydraulic behaviours, such as natural circulation and heat removal capability, were numerically analysed in C++ code, especially for the bayonet cooling thimble. The results show that this system can effectively remove the decay heat in the molten salt in MSRE and has a heat removal rate close to the decay heat generation rate, thus causing the temperature of the molten salt to decrease stably. The width of the gas gap in the bayonet cooling thimble has little effect on the heat exchange or natural circulation inside the thimble, while the width of the vapour riser, although it has little effect on the heat transfer of the system, greatly affects the natural circulation. With the vapour riser width increasing from 3.6 to 5.1 mm, the mass flow rate increases from 1.9 kg/s to 4.79 kg/s. Finally, three operational schemes are proposed for the passive residual heat dissipation system, among which reducing the thimble cooling thimble to three quarters results in comprehensive performance.